The parental reflective functioning questionnaire: Development and preliminary validation - Luyten, Patrick; Mayes, Linda C.; Nijssens, Liesbet; Fonagy, Peter (PLOS ONE, 2017)
This paper reports on three studies on the development and validation of the Parental Reflective Functioning Questionnaire (PRFQ), a brief, multidimensional self-report measure that assesses parental reflective functioning or mentalizing, that is, the capacity to treat the infant as a psychological agent. Study 1 investigated the factor structure, reliability, and relationships of the PRFQ with demographic features, symptomatic distress, attachment dimensions, and emotional availability in a socially diverse sample of 299 mothers of a child aged 0–3. In Study 2, the factorial invariance of the PRFQ in mothers and fathers was investigated in a sample of 153 first-time parents, and relationships with demographic features, symptomatic distress, attachment dimensions, and parenting stress were investigated. Study 3 investigated the relationship between the PRFQ and infant attachment classification as assessed with the Strange Situation Procedure (SSP) in a sample of 136 community mothers and their infants. Exploratory and confirmatory factor analyses suggested three theoretically consistent factors assessing pre-mentalizing modes, certainty about the mental states of the infant, and interest and curiosity in the mental states of the infant. These factors were generally related in theoretically expected ways to parental attachment dimensions, emotional availability, parenting stress, and infant attachment status in the SSP. Yet, at the same time, more research on the PRFQ is needed to further establish its reliability and validity.